An investigation of Iranian learner`s utilization of politeness strategies and power relation in refusal speech act across different communicative situations - Farashaiyan, Atieh; Muthusamy, Paramasivam (Canadian Center of Science and Education, 2017)
This study aimed to examine the L2 pragmatic knowledge of Iranian intermediate learners of English through the performance of the speech act of refusals in English across diverse situations. One hundred and twenty five Iranian learners whose language proficiency was at the intermediate level took part in this research. The required data were collected by mean of an Oxford Placement Test (OPT) and a Written Discourse Completion Task (WDCT). The results showed that most respondents tended to use more indirect strategies (55.5%) to refuse another speaker’s suggestion or request either with higher or lower power or within different social distance. They utilized direct strategies with 24.1% and adjuncts to refusals with 18.9% respectively. The findings are illustrative of the fact that the variations in the use of different strategies are less seen in the data. In other words, learners employed almost the same semantic formulas or pragmalinguistic forms to refuse affairs in most of the situations. It can be said that learners might not have enough awareness or consciousness regarding the use of different pragmalinguistic forms in performing the refusal since they did not have sufficient understanding of context and contextual factors involved as well. Therefore, the results can suggest that the learners lack sufficient pragmatic knowledge in confronting different situations. The implication of this study is for Iranian language instructors to teach a variety of speech acts’ strategies, politeness strategies and draw learners’ their attention to the contextual features in opting out the appropriate strategy in a variety of situations.